Adoption of Organic Vegetable Program Innovation in Organic Vegetable Village - Triyono, Agus; Pangestu, Febryanto (Universitas Muhammadiyah Surakarta, 2020)
The unused land management as the seeding place is a new innovation by the farmers. Alms house is the initiator of the organic village program idea in Ngemplak Sutan Village, Mojosongo, Jebres, Surakarta. Innovation adoption program is started in 2013 and the successful of the program in 2018. It is needed 5 years to change the people’s mindsets to go organic farming. The aim of this research is to know how the process of innovation adoption program of organic vegetables in Ngemplak Sutan Village, Mojosongo, Jebres, Surakarta. The method which is used is qualitative research method since it emphasizes the direct observation and the data is analyzed by non-statistics. The data of this research comes from the primary source, that is deeply interviewed, while the secondary source comes from document, photo, video, and journal which is related with the research. This research uses interactive analyze data technique. The determination of the informant uses snowball sampling. The result of the research shows that the adoption process occurs through particular steps. On the knowledge step, it gives big impact on the decision of do the innovation adoption. This step can change the people’s mindset so they feel interest to do adoption. Innovation adoption program also gives impact on healthy sector, education sector, and economy sector. The conclusion is the adoption process was slow. The education sector is being the determination of the way in adoption process. Experience and knowledge, and the impact which is felt will be important considerations.